Diseño de un sistema híbrido de calentamiento de agua por energía solar y vapor para el Hospital "Isidro Ayora" de la ciudad de Loja. - Jumbo Sarango, Eduardo Patricio (2013)
This study treat of the use of solar energy for hot-health water production, with the help of steam produced by boilers, to get energetic contribution to the daily consumptions of the Hospital Regional "Isidro Ayora", also to supply a service that this medical center does not have, observing it from the centralized point of view,Because that is necessary at departments where there are individual systems. The building consists of five plants with approximately 250 beds and in the majority the hot water is required, whose demand varies throughout the year, but for the subjects of calculation he has been realized with average values. The task contain the design of a net of distribution of hot water that goes through the building supplying 156 sanitary fittings, a water heating system where the energy of solar contribution will be collected by 82 solar panels, and supportive energy will be given by the heat of the vapor generated in the boilers, it also consists the selection of four pumping teams, and a storage system of 7500 liters of ACS , distributed in three similar capabilities tanks, finalizing with an analysis determined of energetic possible saving that it would be gotten , whose value has projected in a 40 % , and the saving in CO2 emissions.